2019
DOI: 10.1111/bjep.12280
|View full text |Cite
|
Sign up to set email alerts
|

The development of children's epistemic beliefs across the early years of elementary school

Abstract: Background.A growing body of research shows that the beliefs we hold about the nature of knowing and knowledge (epistemic beliefs) may mediate moral reasoning. However, a limitation of much of the research in the area of epistemic beliefs is the lack of a longitudinal approach.Aims. The study investigated longitudinal changes in Australian elementary school children's beliefs about knowing and knowledge (epistemic beliefs) across three judgement domains (personal taste, ambiguous facts, and moral values).Sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…A thorough search of the literature indicated that the studies in which children's (preschool-primary schoolmiddle school) epistemological beliefs were measured through vignette-based scenarios adopted unidimensional developmental models (Kuhn et al, 2000;Mansfield & Clinchy, 2002;Sandoval & Cam, 2011;Wainryb et al, 2004;Walker et al, 2019;Wildenger et al, 2010). Holschuh (1998), in his study based on the multi-dimensional epistemological belief model, measured epistemological beliefs through scenarios.…”
Section: Measuring Middle School Students' Epistemological Beliefs: An Approach Based On Vignettes and Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough search of the literature indicated that the studies in which children's (preschool-primary schoolmiddle school) epistemological beliefs were measured through vignette-based scenarios adopted unidimensional developmental models (Kuhn et al, 2000;Mansfield & Clinchy, 2002;Sandoval & Cam, 2011;Wainryb et al, 2004;Walker et al, 2019;Wildenger et al, 2010). Holschuh (1998), in his study based on the multi-dimensional epistemological belief model, measured epistemological beliefs through scenarios.…”
Section: Measuring Middle School Students' Epistemological Beliefs: An Approach Based On Vignettes and Scenariosmentioning
confidence: 99%
“…In most of these studies, the samples consisted of pre-school and primary school students. In the studies, the students were asked to state the views of which character they agreed with and why (Kuhn et al, 2000;Mansfield & Clinchy, 2002;Wainryb et al, 2004;Walker et al, 2019;Wildenger et al, 2010). In the present study, we created imaginary characters representing two opposite poles (naïve-sophisticated) of the five dimensions of epistemological beliefs in Schommer's (1990) model.…”
Section: Creation Of Vignette-based Scenarios and Item Poolmentioning
confidence: 99%